Findings of pilot study following the implementation of point of care intraoperative PTH assay using whole blood during surgery for primary hyperparathyroidism - Mohan Kumar, Rahul; Pannu, Arslan; Metcalfe, Emily; Senbeto, Mesfin; Balasubramanian, Saba P. (Frontiers in Endocrinology, 2023)
Objective: To report findings of pilot study using a novel point of care (POC) intraoperative parathyroid hormone (IOPTH) assay for parathyroid hormone (PTH) using whole blood during surgery for primary hyperparathyroidism (PHPT).Methods: Patients undergoing surgery for primary hyperparathyroidism from March to November 2022 where intraoperative PTH assay was performed using the NBCL CONNECT IOPTH and the laboratory PTH assay were included (group 1). The biochemistry results were reviewed to determine concordance between NBCL and lab PTH values and diagnostic test parameters of the NBCL CONNECT assay. 'In-theatre' times were then compared with a historical cohort (group 2) where the lab-based IOPTH assay alone was used.Results: Of the 141 paired samples in group I, correlation between NBCL and the lab assay was high (rho=0.82; p<0.001). PTH levels using the NBCL assay dropped satisfactorily (>50% of the basal or 0 min sample; whichever was loweri.e. positive test) in 23 patients; giving a positive predictive value of 100%. Of the 9 patients that did not demonstrate a drop, two were true negative (negative predictive value of 22%) leading to cure after excision of another gland.Group 1 (150 mins) had a significantly shorter 'in-theatre' time compared to group 2 (167 mins) (p=0.007); despite much higher use of near infra-red autofluorescence (NIRAF) (72% vs 11.6% in group I and 2 respectively).The NBCL CONNECT POC IOPTH assay gives comparable results to lab based PTH assays and can be performed without need for a centrifuge or qualified technicians. Surgeons, however, need to be aware of the potential for false-negative results.